Addressing a Crisis in Abortion Access: A Case Study in Advocacy. Issue 1 (7th July 2022) - Lynch, Beatrice; Mallow, Michaela; Bodde, Katharine E. S.; Castaldi-Micca, Danielle; Yanow, Susan; Nádas, Marisa
Abstract : Health care systems can ensure that high-quality abortion care is available to all by identifying and removing barriers to services in collaboration with local advocates. Abstract : As restrictions on abortion increase nationwide, it is critical to ensure ongoing access to abortion care throughout pregnancy. People may seek abortions later in pregnancy as a result of financial or legal barriers that delay care or because of changing circumstances, such as the status of their partner, the health of other children, employment, or a new fetal diagnosis. New York State has been a beacon for abortion access since 1970. Yet, after Roe v Wade was decided, New York State abortion law was not in compliance with federal law, and risk-averse medical institutions hesitated to provide later abortions, forcing patients out of state for care. After years of advocacy, the Reproductive Health Act was passed in 2019. Clinicians and advocates collaborated to translate policy into expanded practice at NYC Health + Hospitals, the largest public health care system in the United States. NYC Health + Hospitals conducted an internal review, identified barriers to abortion care, and addressed these through improvements in public and internal communication, strengthening of procedural skills, and a better referral system. As a result, abortion services have become visible and the system's capacity and gestational age limit have expanded. The example of NYC Health + Hospitals is an instructive model to ensure that abortion care is provided to the most vulnerable patients, including those who need care later in pregnancy. Given the ongoing threat to reproductive rights, this example of expanded access is particularly timely.